Comparison of pediatric performance athlete injuries presenting to emergency departments. Issue 1 (2nd January 2023) - Farooqi, Ali; Talwar, Divya; Tata, Ravi; Harwood, Kathleen; Maguire, Kathleen
ABSTRACT: Objective: Pediatric injuries in performance sports represent a significant healthcare burden and account for over 50, 000 annual Emergency Department (ED) visits in the United States. The objective of this study was to characterize and compare pediatric injury presentation across the most common performance sports. Methods: The National Electronic Injury Surveillance System (NEISS) database was retrospectively analyzed for pediatric injuries (3–18 years) related to gymnastics, dance, or cheerleading from 2015–2019. Cases were categorized as children (˂11 years) or adolescent (≥11 years). Injuries were categorized as orthopedic (fractures, dislocations, sprain, strains), non-orthopedic (contusion, internal injury, laceration), concussion, or other/unknown. Case narratives were used to categorize mechanism of injury as contact or non-contact. Appropriate sample NEISS weights estimation was applied for statistical analysis and Confidence Intervals (CI). Results: A total of 393, 110 injuries were observed over the five-year study period, with a mean of 78, 622 annual injuries. Gymnastics, dance, and cheerleading accounted for 136, 422 injuries, 96, 416 injuries, and 160, 272 injuries, respectively. Most cases were adolescent (71%; 95% CI: 68–74%) and occurred in a sports-related setting (65%, 95% CI: 57–72%). Gymnastics had the highest proportion of injuries among children (50%) as compared to dancers (25%) or cheerleaders (12%) (p < 0.01). Non-contact injuries most affected the lower extremity (43–68%) and resulted in an orthopedic diagnosis (63–71%), and contact injuries had a higher proportion of injuries affecting the head, neck, and face (29–51%) and non-orthopedic diagnoses (29–38%). Gymnastics had the most upper extremity non-contact injuries (42%) and dance the most lower extremity non-contact injuries (68%) (p < 0.01). Cheerleading had the highest incidence of overall concussions (8%), contact injuries (47%), and concussions due to contact injury (15%). Conclusion: Pediatric gymnasts, cheerleaders, and dancers have important similarities and differences in injury pattern which may lead to the development of sport-specific injury prevention programs for pediatric performance athletes.